Hubungan Peran Kader Posyandu Balita dengan Motivasi Ibu Melaksanakan Imunisasi Dasar Lengkap: The Relationship of the Role of Integrated Service Pos Cadres for Toddlers with Motivation Mother Does Complete Basic Immunization - Rabiatunnisa Rabiatunnisa; Mujahadatuljannah Mujahadatuljannah; Takesi Araya; Mitha Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Posyandu cadres for toddlers are the main pillars of development, especially in the health sector. However, what often happens is that mothers' motivation is still low in carrying out complete basic immunizations for their toddlers; therefore, if it occurs continuously, it can result in the death of the toddler. This study was conducted to determine the role of Posyandu cadres under five with mother's motivation to carry out complete basic immunization in the Work Area of the UPT Puskesmas Pahandut Palangka Raya. The design used in this study is a correlational research design. Sampling using purposive sampling. The population in this study was mothers who had babies (0-11) months. The sample is 34 respondents in the work area of the UPT Puskesmas Pahandut Palangka Raya. The results of data analysis that have been statistically tested using the SpearmanRank method, it is known from 34 respondents that p = 0.000, significance value = 0.005, then the p value is smaller than the limit of significance value = 0.000 < 0.005, then the Ho hypothesis is rejected (no relationship), H1 is accepted there is a relationship with the strength of the relationship 0.617 high correlation. The results of the SpearmankRank test show that there is a relationship between the role of Posyandu cadres for toddlers and the motivation of mothers to carry out complete basic immunization in the work area of the UPT Puskesmas Pahandut Palangka Raya. From this research, it can be concluded that there is a relationship between the role of Posyandu cadres for toddlers and mothers' motivation to carry out complete basic immunization.